PARTISIPASI ANGGARAN, KETIDAKPASTIAN TUGAS, PENGGUNAAN INFORMASI AKUNTANSI UNTUK EVALUASI KINERJA DAN PERILAKU MANAGERIAL - Susanto, Yulius Kurnia (Jurnal Akuntansi dan Keuangan Indonesia, 2008)
The role of accounting information (such as budget) in performance evaluation (reliance on accounting performance measures or RAPM) can cause managers feeling tension so that managers will negatively be have such as manipulating data and statement. This negative behavior is due to manager ’s desire to get reward as much as possible. The main objective of this research is to examine the moderating effect of budgetary participation and task uncertainty on the relationship between RAPM and manager ’s behavior. Data were drawn through questionnaire survey from Indonesian manufacturing companies. Further, the collected data were analyzed using a moderated regression analysis. The results show that the higher the budgetary participation, the more negative is the relationship between RAPM and manager’s behavior. On the contrary the effect of task uncertainty on the relationship between RAPM and manager ’s behavior is not significant. The research implication is that superior manager needs to pay attention to subordinate manager ’s involvement on budget preparation when his/her performance is evaluated using accounting information so that dysfunctional behavior of subordinate manager can be minimized.